Design and Evaluation of a Method for Over-The-Air Firmware Updates for IoT Devices - Sousa, Maria Júlia Berriel de; Borin, Juliana Freitag (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2023)
Internet of Things (IoT) has been gaining a lot of attention in the last few years and despite the large amount of investments, there are still many challenges to be overcome within all parts of IoT architecture. One challenge is how to develop a long-lasting application. With regard to devices, one of the main contributors to longevity is the ability to update devices firmware. In practical terms, software and firmware updates over-the-air (OTA) are a crucial part of IoT architecture, along with the capacity to manage them remotely. This dissertation explains the IoT architecture with a layered approach and how updates OTA are part of it. As a solution to this problem, the design and implementation of an OTA firmware update method is presented. The method is based on the standard architecture recently proposed by the Internet Engineering Task Force (IETF), in the form of RFC 9019. The proposed solution is evaluated through two testbeds: one with 20 constrained IoT devices connected to an open source IoT cloud platform through a WiFi network and the other one with a set of 75 devices spread in a large geographic area as part of a real world application. Results show that the proposed solution is suitable for constrained devices and has little impact on the network traffic.